Conceptual Model of Technology-Enabled Creative Learning Community - Dawam Dwi Jatmiko Suwawi (Techno.Com, 2017)
This paper proposes a definition of Creative Learning Community (CLC) that is enabled with technology and its conceptual model in Graduate School of Telkom University. As rooted to learning community term, CLC is defined as a teaching and learning approach within a learning community that consists of a group of students and faculty member that uses creative learning concept. This study adapts the Design Science Research Framework in Information System by Hevner et al to build the conceptual model. First, the study synthesizes existing literature on learning community and creative learning community to define CLC term. Second, based on a review of previous studies and books on learning community, creative thinking, group creativity, engaged learning, student learning outcomes and technology supporting creative learning community, the author analyzes construct candidates of the model. Third, after selecting constructs from the candidates, the study continues by designing the conceptual model of technology-enabled creative learning community. The model was tested the implementations of learning community in Graduate School of Telkom University. The findings provide several conceptual and managerial insights into the role of technology in supporting creative learning community. Future work will need to evaluate the model in the context of other engineering.